Minimally invasive procedures for the management of female pattern hair loss - Melo, Daniel Fernandes; Cortez de Almeida, Rita Fernanda; Frattini, Simone Carolina; Santos, Leopoldo Duailibe Nogueira; Ramos, Paulo Müller [UNESP] (Wiley, 2022)
Background: Female Pattern Hair Loss (FPHL) is one of the most common types of hair loss in women. It is characterized by progressive follicular miniaturization leading to diffuse hair thinning over the midfrontal scalp with a negative impact on quality of life. Pharmacological treatments are commonly used, and hair follicle transplantation is an option for those cases with adequate donor area. Minimally invasive procedures, such as microneedling, mesotherapy, microinfusion of drugs into the scalp with tattoo machines (MMP®), and platelet-rich plasma (PRP) have been reported as adjuvant treatments. Aims: This study aims to summarize and discuss the efficacy of minimally invasive procedures described for the management of FPHL. Methods: Published articles indexed on the Pubmed database and Scopus that described minimally invasive procedures for the management of FPHL in humans were considered. Citations were reviewed and added for completeness. The search was for articles in English only. After excluding duplicate titles, 23 relevant articles were considered. Conclusion: Minimally invasive procedures are promising options and may play a role in FPHL treatment. They can be used as adjunctive therapy for FPHL, in case of poor response to clinical therapy, or when patients prefer other care than the standard. We reinforce that these methods should be performed by an experienced medical professional following strict aseptic techniques. However, microneedling, mesotherapy, MMP, and PRP lack standardization and are supported by a low level of evidence yet. For the future, larger randomized clinical trials are essential to determine the efficacy and optimal protocols for these treatments.
Keywords: androgenetic alopecia; female pattern hair loss; mesotherapy; microneedling; procedures